Development of Advanced Tools for Cryogenic Integration - Bugby, D C; Marland, B C; Stouffer, C J; Kroliczek, E J (Advances in Cryogenic Engineering; Volume 49B, 2004)
This paper describes four advanced devices (or tools) that were developed to help solve problems in cryogenic integration. The four devices are: (1) an across-gimbal nitrogen cryogenic loop heat pipe (CLHP); (2) a miniaturized neon CLHP; (3) a differential thermal expansion (DTE) cryogenic thermal switch (CTSW); and (4) a dual-volume nitrogen cryogenic thermal storage unit (CTSU). The across-gimbal CLHP provides a low torque, high conductance solution for gimbaled cryogenic systems wishing to position their cryocoolers off-gimbal. The miniaturized CLHP combines thermal transport, flexibility, and thermal switching (at 35 K) into one device that can be directly mounted to both the cooler cold head and the cooled component. The DTE-CTSW, designed and successfully tested in a previous program using a stainless steel tube and beryllium (Be) end-pieces, was redesigned with a polymer rod and high-purity aluminum (Al) end-pieces to improve performance and manufacturability while still providing a miniaturized design. Lastly, the CTSU was designed with a 6063 Al heat exchanger and integrally welded, segmented, high purity Al thermal straps for direct attachment to both a cooler cold head and a Be component whose peak heat load exceeds its average load by 2.5 times. For each device, the paper will describe its development objective, operating principles, heritage, requirements, design, test data and lessons learned.